Antitumor treatment and cardiohemodynamics in patients with multiple myeloma depending on renal function - B. B. Samura; M. O. Panasenko (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
Purpose – to evaluate the relations of antitumor treatment and cardiohemodynamics in patients with multiple myeloma depending on renal function.